The Efficacy of Couple-Based Interventions on Health-Related Quality of Life in Cancer Patients and Their Spouses: A Meta-analysis of 12 Randomized Controlled Trials. Issue 1 (January 2017) - Wang, FuZhi; Luo, Dan; Fu, Lianguo; Zhang, Hao; Wu, Shuyin; Zhang, Min; Zhou, Huan; Sun, Ting; Chen, Xingzhi
Abstract : Background: Couple-based interventions on health-related quality of life (HRQoL) of cancer patients and their spouses have received increasing attention in recent years, but the findings of previous studies are inconsistent. Objective: The aim of this study was to investigate the effects of couple-based interventions on the HRQoL of cancer patients and their spouses using a meta-analysis approach. Method: English- and Chinese-language publications were collected from PubMed, EBSCO, EMBASE, CMB, and CNKI. The outcome measures included physical health, depression, anxiety, hopelessness, and marital satisfaction (MS). Pooled, weighted mean differences and 95% confidence intervals were estimated using fixed- and random-effects models. Publication bias and sensitivity analyses were performed. Results: Twelve randomized controlled trials were included in this study. Compared with the control groups, the weighted mean differences of depression, anxiety, and MS were significantly improved in the intervention groups. However, improvements in the measures of physical health and hopelessness were nonsignificant. Psychoeducational interventions yielded a larger effect size than did skill training and blending interventions. Publication bias was not significant, and a sensitivity analysis indicated that the results were robust. Conclusions: Couple-based interventions can improve anxiety, depression, and MS among cancer patients and their spouses, and psychoeducational interventions may be an effective approach. Given the small number of studies utilized in this analysis, the results should be considered preliminary and interpreted with caution. Implications for Practice: Couple-based interventions may be an adjunctive method for cancer patients and their spouses to improve HRQoL. Further study concerning couple-based skill training and blending intervention are needed to better understand intervention effects.